Universidade empreendedora: proposi????o de um modelo para as institui????es de ensino superior p??blicas brasileiras - Ruiz, Sofia Maria de Ara??jo (2018)
The concept of entrepreneurial university has received considerable attention in the last decades, mainly by the empirical studies that show the commercial entrepreneurship, whose research development is applied to the demands of the industry, noting that there are gaps on other aspects of entrepreneurship, such as social or for example, that meet the different demands for solutions to problems in society and integrate the entrepreneurial practices between teaching, research, extension and innovation within an entrepreneurial ecosystem. The purpose of this study was to propose a university model that contemplates elements and guidelines, aiming at the transformation of traditional Brazilian public universities into entrepreneurs. For that, a qualitative research of exploratory methodological approach and case study with units of analysis (management, nucleus of technological innovation, academic units and ecosystem) in a Brazilian public university was adopted. After a systematic review of the literature since the seminal studies on entrepreneurial universities, a Brazilian university was selected that was better scored in the national and international rankings to compose the sample, in order to identify such practices extracted from the proposed theoretical model after the literature review. For data collection, semistructured interviews were used as primary data, and as secondary, documentary survey, using as reference the theoretical model based on bibliographic mapping. In the content analysis, we tried to interpret the descriptive-explanatory process about the dimensions that make up an entrepreneurial university to propose the model. At the end, when presenting and discussing the proposal of an exploratory model for the transformation of traditional universities into entrepreneurs, the field revealed that the analyzed university is still in the process of transforming into an entrepreneurial university and, for that, it is necessary to devise strategies, in set. In addition to giving new meaning to the concept of entrepreneurial university, reorganizing the characteristics into dimensions and suggesting guidelines, this study presents the understanding that different areas of knowledge can incorporate extension activities and contribute to the transformation of traditional universities into entrepreneurs and, starting point for other empirical studies